Kekuatan Integrated Communication untuk Membangun Reputasi dalam Menghadapi Krisis - Deni Yanuar (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2017)
The crisis is a thing that must be considered by an institution or a company because the crisis will have an impact on the decline of reputation. But the crisis can also be an opportunity to recognize the organization in improving the quality of the organization, both in internal and external performance. This article aims to describe how to build a reputation for the strength of Integrated Communication (IC) to face future crises. Reputation should be built as early as possible to become a weapon against future crises. Institutions should be able to integrate all the components within the elements of communication and build good relationships with existing stakeholders. Building strategic relationships with stakeholders can be achieved by making innovations to overcome crisis management in their organizations. One of the efforts is to focus more on Integrated Marketing Communications.